Monitoring Translation Lookahead Buffers to Detect Code Injection Attacks. - Ahn, Youngjung; Lee, Yongsuk; Choi, Jin-Young; Lee, Gyungho; Ahn, Dongkyun (Computer (00189162), 2014)
By identifying memory pages that external I/O operations have modified, a proposed scheme blocks malicious injected code activation, accurately distinguishing an attack from legitimate code injection with negligible performance impact and no changes to the user application.